Synchronous Virtual Learning in Ubiquitous Learning Paradigm and Effective Mathematics Teaching - Sabainah Oyebola Akinoso (Babes-Bolyai University, 2024)
Learning generally has taken a new dimension in this present era. Virtual learning has become increasingly popular recently due to technological advancement. Learning has moved from didactic pedagogy characterized by a teacher-centered approach where knowledge is transmitted from the instructor to the learner to a virtual, mobile, blended/ hybrid, e-learning mode of instruction. Learning is now a form of a Transformative approach to teaching and learning that goes beyond acquiring knowledge and skills only to create profound changes in individuals' beliefs, attitudes, values, and behavior. To obtain the necessary skills required for learning, the learners should have access to learning, and learning should be flexible and occur anywhere anytime through virtual instruction. The study emphasizes the ubiquitous (u-learning) paradigm, synchronous virtual learning in particular, and teachers' role in mathematics teaching and learning. This research has contributed valuable insights into how synchronous virtual learning can improve mathematics teaching and learning, support diverse learners, and inform instructional practices in digital environments. The implication of using synchronous virtual learning is to promote active engagement, social interaction, and peer collaboration, enhancing student comprehension and problem-solving skills. Since learning cannot be limited to didactic instruction, virtual learning should be considered for effective mathematics learning.